The wife’s financial liability in Islamic jurisprudence (Journal of the College of Basic Education, 2022)
The Sharia’s interest in money has been a great concern, and in the purposes of Sharia, saving money is one of the five necessities, for this reason, the provisions have been initiated to regulate financial transactions at all levels, individuals and countries, and the financial transactions of the wife were among the priorities of these legislation, detailing her own liability and its connection to the custodian The husband or everything that surrounds her, and in this is evidence of the perfection of the wise Sharia. He did not leave a detail except that he had a share of his satisfaction. As for the previous legislation, in addition to underestimating the entity of the woman, they did not do justice to her in her financial liability, and the topic included three investigations that I talked about in the first topic about Dhimma, its linguistic and idiomatic meaning, and its most important features. In the second topic, it clarifies its meaning in Islamic jurisprudence and its relationship to the eligibility for obligation. In the third topic, the wife’s financial responsibility and related provisions are clarified